Elucidation of Characteristic Sulfur-Fumigated Markers and Chemical Transformation Mechanism for Quality Control of Achyranthes bidentate Blume Using Metabolome and Sulfur Dioxide Residue Analysis - Kang, Chuanzhi; Zhao, Dan; Kang, Liping; Wang, Sheng; Lv, Chaogeng; Zhou, Li; Jiang, Jing-Yi; Yang, Wanzhen; Li, Jiaxing; Huang, Lu-Qi; Guo, Lanping (Frontiers in Plant Science, 2018)
Achyranthes bidentata Blume (AB) is a health food and a sulfur-free herbal medicine that is one of the most heavily sulfur-fumigated herbs in the marketplace. In this work, a comprehensive approach using ultra-performance liquid chromatography coupled with quadrupole time-of-flight-MS (UPLC-Q-TOF-MS) and multivariate statistical analysis was developed to identify characteristic sulfur-fumigation markers, elucidate chemical transformation mechanisms and characterize the degree of sulfur-fumigation of AB. Non-fumigated and sulfur-fumigated AB samples were compared by UPLC-Q-TOF-MS/MS analysis. Three triterpene saponins (Betavulgarosides II–IV) and two amides (Feruloyl-4-O-methyldopamine and Moupinamide) were identified as characteristic markers, which were positively correlated with two active AB components, namely oleanic acid and ferulic acid, respectively. Moreover, the extent of the sulfur-fumigation under different weight ratios of sulfur to herbal materials (1:20, 1:40, and 1:80) was analyzed based on chemical transformations and sulfur dioxide residues. Further verification showed that the ratio of 1:40 within 1 h was reasonable and efficient for herb quality preservation and assurance. This study provides a reliable sulfur-fumigation protocol for the quality control of AB and other herbs.